PENGELOLAAN DAN PENATAAN ARSIP AKTIF DAN INAKTIF - Munadi, Munadi - (Politeknik Negeri Semarang, 2013)
A file is a record of activities in a variety of forms and media in accordance with the development of technology, information and communication which was made and received by the person who create the files in the implementation of social life, state and nation. Based on the functions and uses of file, files can be devided into dynamic and static file. Improper file handling would give some effects to the process of the activities in its organization or institutions.The records and archieves need management’s attention, qualified human resources and adequate place as well. File regulation in Indonesia are regulated in Law number 43 of 2009.